2018
DOI: 10.1002/jcp.27205
|View full text |Cite
|
Sign up to set email alerts
|

The potential therapeutic use of renin–angiotensin system inhibitors in the treatment of inflammatory diseases

Abstract: Inflammation is a normal part of the immune response to injury or infection but its dysregulation promotes the development of inflammatory diseases, which cause considerable human suffering. Nonsteroidal anti-inflammatory agents are the most commonly prescribed agents for the treatment of inflammatory diseases, but they are accompanied by a broad range of side effects, including gastrointestinal and cardiovascular events. The renin-angiotensin system (RAS) is traditionally known for its role in blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 149 publications
(308 reference statements)
1
34
0
1
Order By: Relevance
“…For example, when the renal blood flow is reduced, the kidneys' juxtaglomerular cells secrete renin directly into the blood circulation. This secreted renin converts angiotensinogen released by the liver to be angiotensin1 (Ang1), which is then converted to be angiotensin2 (Ang2) by ACE in pulmonary vascular endothelial cells [117,118,123]. Ang2 plays a central role in the RAS by acting on the angiotensin type 2 receptors AT1R and AT2R.…”
Section: The Physiology Of the Renin-angiotensin System And Ace2mentioning
confidence: 99%
“…For example, when the renal blood flow is reduced, the kidneys' juxtaglomerular cells secrete renin directly into the blood circulation. This secreted renin converts angiotensinogen released by the liver to be angiotensin1 (Ang1), which is then converted to be angiotensin2 (Ang2) by ACE in pulmonary vascular endothelial cells [117,118,123]. Ang2 plays a central role in the RAS by acting on the angiotensin type 2 receptors AT1R and AT2R.…”
Section: The Physiology Of the Renin-angiotensin System And Ace2mentioning
confidence: 99%
“…A previous study has reported an RAS alternation in neural differentiation and several pathologic conditions such as MS [10,11]. e idea of measuring serum ACE levels in ON is associated with studies investigating the role played by RAS axis and angiotensin in autoimmune and inflammatory diseases [12][13][14][15]. In some studies, RAS and related factors such as angiotensin I, angiotensin II, and serum ACE were claimed to be one of the key elements affecting and regulating inflammatory responses in the brain [16].…”
Section: Introductionmentioning
confidence: 99%
“…The most widely used antihypertensive drug classes, angiotensin‐converting enzyme inhibitors and Ang‐II receptor blockers (ARBs), are used to treat inflammatory diseases through actions independent of their effects on blood pressure (Ranjbar et al ). Of notice, AT1R are up‐regulated in inflamed tissues.…”
mentioning
confidence: 99%